Magnetic biomaterials and nano-instructive tools as mediators of tendon mechanotransduction. Issue 1 (23rd December 2019) - Matos, Ana M.; Gonçalves, Ana I.; El Haj, Alicia J.; Gomes, Manuela E.
Abstract : This review identifies the latest advances and potential of magnetically actuated biomaterials within the scope of tendon tissue engineering. Abstract : Tendon tissues connect muscle to bone allowing the transmission of forces resulting in joint movement. Tendon injuries are prevalent in society and the impact on public health is of utmost concern. Thus, clinical options for tendon treatments are in demand, and tissue engineering aims to provide reliable and successful long-term regenerative solutions. Moreover, the possibility of regulating cell fate by triggering intracellular pathways is a current challenge in regenerative medicine. In the last decade, the use of magnetic nanoparticles as nano-instructive tools has led to great advances in diagnostics and therapeutics. Recent advances using magnetic nanomaterials for regenerative medicine applications include the incorporation of magnetic biomaterials within 3D scaffolds resulting in mechanoresponsive systems with unprecedented properties and the use of nanomagnetic actuators to control cell signaling. Mechano-responsive scaffolds and nanomagnetic systems can act as mechanostimulation platforms to apply forces directly to single cells and multicellular biological tissues. As transmitters of forces in a localized manner, the approaches enable the downstream activation of key tenogenic signaling pathways. In this minireview, we provide a brief outlook on the tenogenic signaling pathways which are most associated with the conversion of mechanical input into biochemical signals, the novel bio-magnetic approaches which can activate these pathways, and the efforts to translate magnetic biomaterials into regenerative platforms for tendon repair.